2022
DOI: 10.20944/preprints202209.0310.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Down-Selection of Repurposed Drug Candidates for COVID-19

Abstract: SARS-CoV-2, is the cause of the COVID-19 pandemic which has claimed more than six million lives worldwide, devastating the economy and overwhelming healthcare systems globally. The development of new drug molecules and vaccines has played a critical role in managing the pandemic; however, new variants of concern still pose a significant threat as the current vaccines cannot prevent all infections. This situation calls for the collaboration of biomedical scientists and healthcare workers across the world. Repur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, the quest to identify potential molecules to treat COVID-19 and PASC is still ongoing. We developed a systematic approach to catalogue all FDA/TGA approved drugs available in the Compounds Australia collection [25]; down-select 214 likely candidates [26]; evaluate in vitro/ex vivo efficacy of the top 12 leads [14]; and screen the 214 candidates using molecular modeling techniques to identify additional leads [27]. In our latter list is present a bisphosphonate molecule called alendronate, and we came across a parallel study which observed that humans who used alendronate (and another bisphosphonate called zoledronate) had lower odds ratios (typically 0.21-0.29) of testing for SARS-CoV-2 infection, COVID-19 diagnosis and COVID-19-related hospitalization [28].…”
Section: Objectives Of This Workmentioning
confidence: 99%
“…Therefore, the quest to identify potential molecules to treat COVID-19 and PASC is still ongoing. We developed a systematic approach to catalogue all FDA/TGA approved drugs available in the Compounds Australia collection [25]; down-select 214 likely candidates [26]; evaluate in vitro/ex vivo efficacy of the top 12 leads [14]; and screen the 214 candidates using molecular modeling techniques to identify additional leads [27]. In our latter list is present a bisphosphonate molecule called alendronate, and we came across a parallel study which observed that humans who used alendronate (and another bisphosphonate called zoledronate) had lower odds ratios (typically 0.21-0.29) of testing for SARS-CoV-2 infection, COVID-19 diagnosis and COVID-19-related hospitalization [28].…”
Section: Objectives Of This Workmentioning
confidence: 99%
“…Visual representation of the filters used to down-select drugs and the filters passed by each drug has been added for those who would like to investigate this further. Drugs are ranked based on activity scores calculated using the assay data as described in MacRaild et al, 2022 [10]. Another important feature of this page is the dynamic calculation and display of similar drug candidates.…”
Section: Drug Overview Pagementioning
confidence: 99%
“…It displays the output along with the number of filters passed out of the total eleven designed by the research team. This computer science paper should be read in conjunction with research by MacRaild et al, 2022 [10], which describes the pharmacological methodology for systematic down-selection of repurposed drug candidates for COVID-19. To increase collaboration with the other researchers, features have been incorporated in CoviRx that allow registered users to submit their findings on any drug candidate to the CoviRx web app.…”
Section: Introductionmentioning
confidence: 99%